2019
DOI: 10.3390/app9081715
|View full text |Cite
|
Sign up to set email alerts
|

The Method of Fundamental Solutions for Three-Dimensional Nonlinear Free Surface Flows Using the Iterative Scheme

Abstract: In this article, we present a meshless method based on the method of fundamental solutions (MFS) capable of solving free surface flow in three dimensions. Since the basis function of the MFS satisfies the governing equation, the advantage of the MFS is that only the problem boundary needs to be placed in the collocation points. For solving the three-dimensional free surface with nonlinear boundary conditions, the relaxation method in conjunction with the MFS is used, in which the three-dimensional free surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have found it difficult to calculate the Jacobian matrix using Newton's method. Thus, the Picard iterative method is used in this study [5]. The Picard iteration first begins from the initial guess of the location for the moving boundary.…”
Section: The Iterative Scheme For Modeling Transient Moving Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found it difficult to calculate the Jacobian matrix using Newton's method. Thus, the Picard iterative method is used in this study [5]. The Picard iteration first begins from the initial guess of the location for the moving boundary.…”
Section: The Iterative Scheme For Modeling Transient Moving Boundarymentioning
confidence: 99%
“…The phreatic line is located between the fluid phase and the air phase of the soil. It is sometimes regarded as the phase change problem [5][6][7]. Phase change problems are often encountered in engineering, industry, and problems such as the design of roadways in cold regions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The other non-linear problem is related to the flow in a porous medium with a free surface. The 3D version of such a flow was considered in [ 36 ]. The problem is the BVP with the Laplace equation and non-linear boundary conditions.…”
Section: Introductionmentioning
confidence: 99%